2014
DOI: 10.3892/ijmm.2014.1869
|View full text |Cite
|
Sign up to set email alerts
|

Achyranthes bidentata polysaccharides activate the Wnt/β-catenin signaling pathway to promote chondrocyte proliferation

Abstract: Achyranthes bidentata polysaccharides (ABPS) are the active components of Radix Achyranthis Bidentatae (AB), which has been extensively used in Traditional Chinese medicine (TCM) in the treatment of osteoarthritis (OA). Our previous study provided evidence that ABPS regulated the G1/S transition to promote chondrocyte proliferation. However, the precise mechanisms involved remain to be elucidated. In the present study, we aimed to investigate the effects of ABPS on the Wnt/β‑catenin signaling pathway in chondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 25 publications
4
42
0
Order By: Relevance
“…The present study showed that several mRNA (MMP-9, MMP-13, BMP-2 and ADAMTS5) are up-regulated and one mRNA (COL2A1) down-regulated in OA compared with normal cartilage. Our findings concerning expression of mRNA are consistent with those of previous studies of OA [27][28][29] . Thus, the present RT-PCR results supported cartilage degeneration in the OA group.…”
Section: Discussionsupporting
confidence: 93%
“…The present study showed that several mRNA (MMP-9, MMP-13, BMP-2 and ADAMTS5) are up-regulated and one mRNA (COL2A1) down-regulated in OA compared with normal cartilage. Our findings concerning expression of mRNA are consistent with those of previous studies of OA [27][28][29] . Thus, the present RT-PCR results supported cartilage degeneration in the OA group.…”
Section: Discussionsupporting
confidence: 93%
“…Several clinical and animal studies provided evidence suggesting that Twotooth Achyranthes Root, Chinese Angelica, Salviae Miltiorrhizae, Safflower and White Peony Root can promote the flow of Qi (vital energy) and blood, and can reduce swelling, remove blood stasis, and bring more nutrients and oxygen to healing tissue (Huang et al , 2014; Lin et al , 2005; Liu et al , 2013; Luo et al , 2013; Magdalou et al , 2015; Wei et al , 1999; Weng et al , 2014; Xie et al , 2001; Zhou et al , 2013). …”
Section: Discussionmentioning
confidence: 99%
“…78 Weng et al 120 studied in rats the component of a plant used in traditional Chinese medicine for the treatment of OA, called Achyranthes bidentata polysaccharides (ABPS) and demonstrated activation of Wnt/β catenin pathway, they also used Western blot for Wnt4, Frizzled 2, β catenin. ABPS seems to have beneficial effects in patients with OA by inducing proliferation of chondrocytes 120 Cassuto et al followed proinflammatory cytokines, anabolic and catabolic pathways in patients following hip arthroplasty. They found increased levels of the anabolic molecules, including Wnt/β catenin, and transient and remodeling activities for Wnt inhibitor molecules (ex.…”
Section: Wnt Signaling Molecules Andmentioning
confidence: 99%